Corrosion inhibition of iron in hydrochloric acid by polyacrylamide - DRAGICA CHAMOVSKA; MAJA CVETKOVSKA; TOMA GRCHEV (Journal of the Serbian Chemical Society, 2007)
The corrosion protection and/or adsorption of polyacrylamide (PAA) of number average molecular weight, , between 15,000 – 1,350,000 g mol-1 on mild steel and iron (99.99 % Fe) in 3 M HCl at room temperature was studied using spectrophotometry (the phenanthroline method), the weight loss method and EIS (Electrochemical Impedance Spectroscopy). It was found that the corrosion protecttion efficiency of the PAA – adsorbed layers strongly depends on both the molar concentration of PAA in the solution and its molecular weight, reaching limiting values between 85 and 96 %. Simultaneously, it was also concluded that a relatively high surface coverage could be obtained with very low PAA concentrations (0.5 – 2 ppm), indicating the good adsorption characteristics of PAA on mild steel and iron in hydrochloride acid. The experimentally obtained results follow a Langmuir adsorption isotherm. According to the best fitting parameters, the adsorption coefficient B ranged between 2×107 and 4×108 mol-1 and depended strongly on the molecular weight of the PAA: B = k (for a ≈ 0.67 and k = 2.95×104) or the size of the polymer coil. As was found by EIS, the thickness of the adsorbed PAA layer was approx. 1.1 nm (for er = 15) and corresponded only to the polymer segments attached to the metal surface. On the other hand, as was found by ellipsometry, the limiting layer of the adsorbed PAA molecules was highly voluminous and relatively thick (100 – 200 nm), containing entangled polymer coils.